2016
DOI: 10.1097/tp.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibition Suppresses Posttransplant Alloantibody Production Through Direct Inhibition of Alloprimed B Cells and Sparing of CD8+ Antibody-Suppressing T cells

Abstract: Background De novo alloantibodies (DSA) contribute to antibody-mediated rejection and poor long-term graft survival. Since the development of DSA is associated with early graft loss of cell transplants and reduced long-term survival of solid organ transplants, we hypothesized that conventional immunosuppressives, calcineurin inhibitors (CNi) and mammalian target of rapamycin inhibitors (mTORi), may not be as effective for suppression of humoral alloimmunity as for cell-mediated immunity. Methods Wild-type or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…It is part of a distinguished group of immunosuppressive drugs that have a divergent mode of action to that of CNIs even though they bind to the identical intracellular immunophilin as tacrolimus, namely, FKBP12. The mTORi/FKBP12 complex binds to and hinders the TORC1 complex, preventing proliferation of numerous cell types, such as T-lymphocytes, alloprimed B cells, and CD8 TAb-supp cells [10, 11]. The side effect profile of EVR is different from that of CNI and includes impaired wound healing, mouth ulcers, stomatitis, arthralgia, hyperlipidemia, and anemia [1215].…”
Section: Introductionmentioning
confidence: 99%
“…It is part of a distinguished group of immunosuppressive drugs that have a divergent mode of action to that of CNIs even though they bind to the identical intracellular immunophilin as tacrolimus, namely, FKBP12. The mTORi/FKBP12 complex binds to and hinders the TORC1 complex, preventing proliferation of numerous cell types, such as T-lymphocytes, alloprimed B cells, and CD8 TAb-supp cells [10, 11]. The side effect profile of EVR is different from that of CNI and includes impaired wound healing, mouth ulcers, stomatitis, arthralgia, hyperlipidemia, and anemia [1215].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody‐producing allospecific B cells play a central role in antibody‐mediated allograft rejection, particularly chronic renal allograft nephropathy . A recent report suggests that mTOR inhibition suppresses not only alloprimed B cells but also antibody‐suppressing CD8 + cells . However, mTOR inhibitor, when use as monotherapy following alemtuzumab induction, does not prevent de novo DSAs and antibody‐mediated rejection .…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] A recent report suggests that mTOR inhibition suppresses not only alloprimed B cells but also antibody-suppressing CD8 + cells. 26 However, mTOR inhibitor, when use as monotherapy following alemtuzumab induction, does not prevent de novo DSAs and antibody-mediated rejection. 11 In contrast, this cohort study demonstrates that B7 costimulation blockade effectively inhibits de novo DSAs.…”
Section: Antibody-producing Allospecific B Cells Play a Central Role mentioning
confidence: 99%
See 1 more Smart Citation
“… showed that knockdown of either mTORC1 and mTORC2 blocked endothelial cell proliferation induced by HLA Class I. In a murine model where mice were transplanted with allogeneic hepatocytes, administration of mTOR inhibitors suppressed alloantibody production by alloprimed IgG1 B cells, an effect that was not observed after calcineurin inhibitor (CNI) administration .…”
Section: Mtor Inhibition and Mediators Of Amr: In Vitro And Preclinical Datamentioning
confidence: 99%